Ο kalvos sta ichni tou 'longinou': Enas anthropos ton grammaton stin evropi tou 19ou aiona ('Kalvos in the footsteps of "Longinus": A man of letters in nineteenth-century Europe'), Angela Yioti (2019). Issue 2 (1st October 2020) - Ricks, David
Review of: Ο kalvos sta ichni tou 'longinou': Enas anthropos ton grammaton stin evropi tou 19ou aiona ('Kalvos in the footsteps of "Longinus": A man of letters in nineteenth-century Europe'), Angela Yioti (2019)Athens: Antipodes, 478 pp., ISBN 978-618-5267-05-6, p/bk, €18.00